Sistem Manajemen Pelayanan Terpadu Satu Pintu (PTSP) dalam Meningkatkan Kinerja Aparatur Pelaksana Pendidikan Islam di MAN 3 Kediri - Moh. Syukron Roziqin; M. Hanif Satria Budi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
One Door Integrated Service Management System (PTSP) In Improving The Performance of Islamic Education Implementing Apparatus In The Ministry of Religious Affairs of MAN 3 Kediri. This research aims to analyze the management system of the One Door Integrated Service (PTSP) in improving the performance of the Islamic education implementing apparatus. PTSP is the product of innovation from the reform of the public service bureaucracy implemented in an integrated and integrated manner for all types of services. This research uses a descriptive qualitative approach, with a research site at the Ministry of Religious Affairs Office of MAN 3 Kediri. This research shows the difference between service conditions before and after the implementation of the PTSP management system. Where previous service conditions were still rigid, and unfocused, it is now becoming more comfortable, faster, transparent, and more focused with regulatory policies, service standards, legal certainty, commitment, and organizational culture as supporting factors in PTSP management system.